Generic drug product development International regulatory requirements for bioequivalence - Kanfer,Isadore; Shargel, Leon, 1941-; Kanfer, Isadore (New York : Informa Healthcare, 2010)
Discusses the worldwide legislative and regulatory requirements for the registration of generic and multi-source drug products.
Includes bibliographical references and index.
Print version also available.
Mode of access: Internet
Keywords: Generic drugs; Generic drugs -- Law and legislation; Drugs, Generic -- pharmacokinetics; Drugs, Generic -- standards; Biological Availability; Drug Design; International Cooperation; Legislation, Drug; Therapeutic Equivalency; Biological availability; Drug design; Drugs, Generic -- Pharmacokinetics; Drugs, Generic -- Standards; Generic drugs -- Law and legislation; Generic drugs; International cooperation; Legislation, drug; Therapeutic equivalency; Pharmacy; Medicine